18.23: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/18.23.E5 18.23.E5] || [[Item:Q5906|<math>e^{z}\left(1-\frac{z}{a}\right)^{x} = \sum_{n=0}^{\infty}\frac{\CharlierpolyC{n}@{x}{a}}{n!}z^{n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>e^{z}\left(1-\frac{z}{a}\right)^{x} = \sum_{n=0}^{\infty}\frac{\CharlierpolyC{n}@{x}{a}}{n!}z^{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || <syntaxhighlight lang=mathematica>Exp[x + y*I]*(1 -Divide[x + y*I,a])^(x) == Sum[Divide[HypergeometricPFQ[{-(n), -(x)}, {}, -Divide[1,a]],(n)!]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Missing Macro Error || - || -
| [https://dlmf.nist.gov/18.23.E5 18.23.E5] || <math qid="Q5906">e^{z}\left(1-\frac{z}{a}\right)^{x} = \sum_{n=0}^{\infty}\frac{\CharlierpolyC{n}@{x}{a}}{n!}z^{n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>e^{z}\left(1-\frac{z}{a}\right)^{x} = \sum_{n=0}^{\infty}\frac{\CharlierpolyC{n}@{x}{a}}{n!}z^{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || <syntaxhighlight lang=mathematica>Exp[x + y*I]*(1 -Divide[x + y*I,a])^(x) == Sum[Divide[HypergeometricPFQ[{-(n), -(x)}, {}, -Divide[1,a]],(n)!]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Missing Macro Error || - || -
|-  
|-  
| [https://dlmf.nist.gov/18.23.E6 18.23.E6] || [[Item:Q5907|<math>\genhyperF{1}{1}@@{a+\iunit x}{2\realpart@@{a}}{-\iunit z}\genhyperF{1}{1}@@{\conj{b}-\iunit x}{2\realpart@@{b}}{\iunit z} = \sum_{n=0}^{\infty}\frac{\contHahnpolyp{n}@{x}{a}{b}{\conj{a}}{\conj{b}}}{\Pochhammersym{2\realpart@@{a}}{n}\Pochhammersym{2\realpart@@{b}}{n}}z^{n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\genhyperF{1}{1}@@{a+\iunit x}{2\realpart@@{a}}{-\iunit z}\genhyperF{1}{1}@@{\conj{b}-\iunit x}{2\realpart@@{b}}{\iunit z} = \sum_{n=0}^{\infty}\frac{\contHahnpolyp{n}@{x}{a}{b}{\conj{a}}{\conj{b}}}{\Pochhammersym{2\realpart@@{a}}{n}\Pochhammersym{2\realpart@@{b}}{n}}z^{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || <syntaxhighlight lang=mathematica>HypergeometricPFQ[{a + I*x}, {2*Re[a]}, - I*(x + y*I)]*HypergeometricPFQ[{Conjugate[b]- I*x}, {2*Re[b]}, I*(x + y*I)] == Sum[Divide[I^(n)*Divide[Pochhammer[a + Conjugate[a], n]*Pochhammer[a + Conjugate[b], n], (n)!] * HypergeometricPFQ[{-(n), n + 2*Re[a + b] - 1, a + I*(x)}, {a + Conjugate[a], a + Conjugate[b]}, 1],Pochhammer[2*Re[a], n]*Pochhammer[2*Re[b], n]]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Missing Macro Error || - || -
| [https://dlmf.nist.gov/18.23.E6 18.23.E6] || <math qid="Q5907">\genhyperF{1}{1}@@{a+\iunit x}{2\realpart@@{a}}{-\iunit z}\genhyperF{1}{1}@@{\conj{b}-\iunit x}{2\realpart@@{b}}{\iunit z} = \sum_{n=0}^{\infty}\frac{\contHahnpolyp{n}@{x}{a}{b}{\conj{a}}{\conj{b}}}{\Pochhammersym{2\realpart@@{a}}{n}\Pochhammersym{2\realpart@@{b}}{n}}z^{n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\genhyperF{1}{1}@@{a+\iunit x}{2\realpart@@{a}}{-\iunit z}\genhyperF{1}{1}@@{\conj{b}-\iunit x}{2\realpart@@{b}}{\iunit z} = \sum_{n=0}^{\infty}\frac{\contHahnpolyp{n}@{x}{a}{b}{\conj{a}}{\conj{b}}}{\Pochhammersym{2\realpart@@{a}}{n}\Pochhammersym{2\realpart@@{b}}{n}}z^{n}</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>Error</syntaxhighlight> || <syntaxhighlight lang=mathematica>HypergeometricPFQ[{a + I*x}, {2*Re[a]}, - I*(x + y*I)]*HypergeometricPFQ[{Conjugate[b]- I*x}, {2*Re[b]}, I*(x + y*I)] == Sum[Divide[I^(n)*Divide[Pochhammer[a + Conjugate[a], n]*Pochhammer[a + Conjugate[b], n], (n)!] * HypergeometricPFQ[{-(n), n + 2*Re[a + b] - 1, a + I*(x)}, {a + Conjugate[a], a + Conjugate[b]}, 1],Pochhammer[2*Re[a], n]*Pochhammer[2*Re[b], n]]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]</syntaxhighlight> || Missing Macro Error || Missing Macro Error || - || -
|}
|}
</div>
</div>

Latest revision as of 11:47, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
18.23.E5 e z ( 1 - z a ) x = n = 0 C n ( x ; a ) n ! z n superscript 𝑒 𝑧 superscript 1 𝑧 𝑎 𝑥 superscript subscript 𝑛 0 Charlier-polynomial-C 𝑛 𝑥 𝑎 𝑛 superscript 𝑧 𝑛 {\displaystyle{\displaystyle e^{z}\left(1-\frac{z}{a}\right)^{x}=\sum_{n=0}^{% \infty}\frac{C_{n}\left(x;a\right)}{n!}z^{n}}}
e^{z}\left(1-\frac{z}{a}\right)^{x} = \sum_{n=0}^{\infty}\frac{\CharlierpolyC{n}@{x}{a}}{n!}z^{n}

Error
Exp[x + y*I]*(1 -Divide[x + y*I,a])^(x) == Sum[Divide[HypergeometricPFQ[{-(n), -(x)}, {}, -Divide[1,a]],(n)!]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]
Missing Macro Error Missing Macro Error - -
18.23.E6 F 1 1 ( a + i x 2 a ; - i z ) F 1 1 ( b ¯ - i x 2 b ; i z ) = n = 0 p n ( x ; a , b , a ¯ , b ¯ ) ( 2 a ) n ( 2 b ) n z n Kummer-confluent-hypergeometric-M-as-1F1 𝑎 imaginary-unit 𝑥 2 𝑎 imaginary-unit 𝑧 Kummer-confluent-hypergeometric-M-as-1F1 𝑏 imaginary-unit 𝑥 2 𝑏 imaginary-unit 𝑧 superscript subscript 𝑛 0 continuous-Hahn-polynomial-p 𝑛 𝑥 𝑎 𝑏 𝑎 𝑏 Pochhammer 2 𝑎 𝑛 Pochhammer 2 𝑏 𝑛 superscript 𝑧 𝑛 {\displaystyle{\displaystyle{{}_{1}F_{1}}\left({a+\mathrm{i}x\atop 2\Re a};-% \mathrm{i}z\right){{}_{1}F_{1}}\left({\overline{b}-\mathrm{i}x\atop 2\Re b};% \mathrm{i}z\right)=\sum_{n=0}^{\infty}\frac{p_{n}\left(x;a,b,\overline{a},% \overline{b}\right)}{{\left(2\Re a\right)_{n}}{\left(2\Re b\right)_{n}}}z^{n}}}
\genhyperF{1}{1}@@{a+\iunit x}{2\realpart@@{a}}{-\iunit z}\genhyperF{1}{1}@@{\conj{b}-\iunit x}{2\realpart@@{b}}{\iunit z} = \sum_{n=0}^{\infty}\frac{\contHahnpolyp{n}@{x}{a}{b}{\conj{a}}{\conj{b}}}{\Pochhammersym{2\realpart@@{a}}{n}\Pochhammersym{2\realpart@@{b}}{n}}z^{n}

Error
HypergeometricPFQ[{a + I*x}, {2*Re[a]}, - I*(x + y*I)]*HypergeometricPFQ[{Conjugate[b]- I*x}, {2*Re[b]}, I*(x + y*I)] == Sum[Divide[I^(n)*Divide[Pochhammer[a + Conjugate[a], n]*Pochhammer[a + Conjugate[b], n], (n)!] * HypergeometricPFQ[{-(n), n + 2*Re[a + b] - 1, a + I*(x)}, {a + Conjugate[a], a + Conjugate[b]}, 1],Pochhammer[2*Re[a], n]*Pochhammer[2*Re[b], n]]*(x + y*I)^(n), {n, 0, Infinity}, GenerateConditions->None]
Missing Macro Error Missing Macro Error - -